The effects of parental autonomy on the creation of STEM career interests - Fazilah Razali; Faiq Aziz; Ahmad Aizuddin Md Rami (Institute of Advanced Engineering and Science, 2022)
This research paper focuses on the effects of the parent autonomy factor that supports the needs of students in science, technology, engineering, and mathematics (STEM) learning and builds the interest of students in STEM careers. This was a quantitative research study that employed the parent authority questionnaire (PAQ). Based on the research objective, the questions in the PAQ were altered to evaluate the effects of parents on student interest in STEM careers and adapted to the purpose of the study. The PAQ comprises a scale of 1-10 ranging from strongly disagree to strongly agree. Research respondents included 419 upper secondary students from national schools in Malaysia, and the research used a proportionate stratified random sampling technique. The research determined parents’ autonomy towards the development of students’ STEM career interest and the data was analyzed using structural equation modelling (SEM). The results found that the autonomy of parents significantly affected upper secondary students in the development of STEM careers of students. The research question was answered by proving that the autonomy of parents is directly significant (p<001). Results showed that parents explicitly offer meaningful impacts and valuable values to motivate students of the science stream at the secondary level to ensure that their STEM career interests are well nurtured. The findings from this research provide useful insight into the learners, and lead to the value of autonomy of parents in promoting a curriculum design that suits the needs of students in the future.